Prevalence of Smokeless Tobacco Usage among Adult Population in Rural Area - Sangeetha R; G Kalyan Chakravarthy; Sunitha Sreegiri (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Tobacco is a leading risk factor for deaths due to non-communicable diseases in developing countries. India accounts for 70% of the global burden of smokeless tobacco which also attributes to 27% of all cancers in India. Tobacco usage is a major public health issue which needs to be addressed effectively. Objectives were to estimate the prevalence of smokeless tobacco usage in study population and to assess awareness regarding the harmful effects of tobacco usage and COTPA in the study population. Methods: A community based cross-sectional study was conducted among all adults aged 18 years & above residing in Chandragiri Mandal during March-April 2025. Using simple random sampling, 190 participants were selected and interviewed using pretested semi- structured questionnaire. Data was entered in MS Excel and analysed using Epi Info software. The differences between the qualitative variables were analysed using Chi-square test. Results: Out of the 190 participants interviewed, 37.9% were using smokeless tobacco at present. Most of the users were above 60 years of age. Smokeless tobacco consumption was more among females. Majority of the participants i.e. 85.1% knew about the harmful effects of tobacco. Almost 44.4% knew about COTPA, 92.9% were in favour of the act and 45.8% believed that pictorial warning helps reduce smokeless tobacco use. Conclusion: Smokeless tobacco usage was higher among females than males and in the older age group (>60 years). Health education and counselling need to be provided regarding the harmful effects of tobacco.